PERANAN RUMAH TANGGA NELAYAN DALAM MENINGKATKAN PENDAPATAN KELUARGA DI DESA PELA KECAMATAN KOTA BANGUN KABUPATEN KUTAI KARTANEGARA - Amiruddin; Dayang Diah Fidhiani; Fitriyana (2339-1324, 2024)
In Pela village, the majority of people work as fishermen. The purpose of this research was to know the roles of fishermen households to raising family income, to know the contribution of the fishermen households income and to know the activity profile and participation of fishermen's wives. The sampling method used the census method with the number of respondents 20 fishermen families. The method of data analysis used a descriptive analysis based on tabulation and qualitative descriptive. The results of the research showed that the fishermen households in Pela village, Kota Bangun Regency of Kutai Kartanegara, the husband of fishermen as the head of the household who had a job as a fish seeker, while a fisherman's wife served as a housewife, which also had the type of work of salty fish processing and crackers. The contributions of fishermen's wife in the family's income reached 31% while the fishermen's husband amounted to 69%. The activity of fishermen's household in the production was more dominant, it reached 53.33% while fishermen wife only 46.67%. On the other hand, the reproduction and social activities of fishermen's wife were more dominant 75.625% and 34.375%, while fishermen's husband 3.125% and 15, 625%. For the participation of access and control of fishermen households, the fishermen's wife was more dominant than the fishermen. Meanwhile, the factors that affect the fishermen family contrainm of (9.17%), and opportunity (75.83%).